Sexual aspects of liver transplant candidates and recipients: evidence available in the literature - Jennifer Tatisa Jubileu Magro; Karina Dal Sasso Mendes; Cristina Maria Galvão (Universidade de São Paulo, 2018)
ABSTRACT Objective: to analyze the evidence available in the literature on the alterations in the sexuality of candidates and recipients of liver transplantation. Method: integrative review of the literature with search for primary studies in the databases MEDLINE (via PUBMED), CINAHL e LILACS, published in English, Portuguese and Spanish. Results: the 16 primary studies included were grouped into three categories: 1) female sexuality (n=5), 2) male sexuality (n=5) and 3) male and female sexuality (n=6). In category 1, the subjects investigated were contraception, pregnancy, sexual dysfunction, presence of gynecological symptoms and sexually transmitted infections. In category 2, the main focus of the studies was erectile dysfunction, sexual desire and satisfaction, and consequences of the immunosuppressive regimen with mycophenolic acid in men. In category 3, the evaluation of sexual function was the main topic. Conclusion: the scientific evidence generated provides support to encourage health professionals to incorporate the topic of sexuality in the routine of care. Knowledge gaps were identified and new studies should be conducted in order to implement interventions to prevent, minimize and/or control changes related to the patient's sexuality.